2021
DOI: 10.3389/fmicb.2021.656302
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-Wide N6-Methyladenosine (m6A) Profiling of Susceptible and Resistant Wheat Varieties Reveals the Involvement of Variety-Specific m6A Modification Involved in Virus-Host Interaction Pathways

Abstract: N6-methyladenosine (m6A) methylation is the most prevalent internal modification of post-transcriptional modifications in mRNA, tRNA, miRNA, and long non-coding RNA in eukaryotes. m6A methylation has been proven to be involved in plant resistance to pathogens. However, there are no reports on wheat (Triticum aestivum) m6A transcriptome-wide map and its potential biological function in wheat resistance to wheat yellow mosaic virus (WYMV). To the best of our knowledge, this study is the first to determine the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 56 publications
2
34
0
Order By: Relevance
“… 2021 ), and recent data indicate it could be effective against potyvirids as supported by reported changes in N 6 -methyladenosine levels upon bymovirus infection (Zhang et al . 2021 ).…”
Section: Immune Evasion Through Leader and Non-core Modules Of Potyvi...mentioning
confidence: 99%
“… 2021 ), and recent data indicate it could be effective against potyvirids as supported by reported changes in N 6 -methyladenosine levels upon bymovirus infection (Zhang et al . 2021 ).…”
Section: Immune Evasion Through Leader and Non-core Modules Of Potyvi...mentioning
confidence: 99%
“…Transcriptome-wide m6A profiling found a significant variation in the m6A modification patterns between the resistant and susceptible wheat varieties. Different m6A RNA modifications in the two varieties demonstrated regulation of gene expression and pathogen–plant interaction-related pathways [ 68 ]. The m6A demethylase activity of atALKBH9B modulates AMV infection and the m6A abundance in its genomic RNAs, indicating that plant m6A methylation might be involved in viral infection [ 50 ].…”
Section: M6a Methylation Is One Of the Defense Mechanisms Against Pla...mentioning
confidence: 99%
“…Among the studied epigenetic modifications, RNA N 6 -methyladosine (m 6 A) modification is the subject of the most up-to-date research, and it is the most prevalent internal post-transcriptional modification of mRNA. In experiments looking into the plant-pathogen arms race, results suggested that m 6 A modification is activated in pathogen-infected plants, which leads to different effects on the m 6 A and mRNA levels of genes related to plantpathogen interaction, indicating a variety-specific m 6 A modification [88,89]. m 6 A has been shown to evolve synchronously with genome evolution and mRNA abundance [90].…”
Section: Epigenetics and R Gene Evolutionmentioning
confidence: 99%